Zakat Funds, Non-Halal Funds, Islamic Social Reporting On The Islamic Commercial Banks Performance And Reputation - Puji Suciarti; Novi Lailiyul Wafiroh (LPPM ISNJ Bengkalis, 2023)
This study aims to show how the influence of zakat funds, non-halal funds, and Islamic social reporting (ISR) on the performance and reputation of Islamic commercial banks. This type of research uses a quantitative approach. The research population is Islamic commercial banks (ICB) in Indonesia registered with the financial services authority (FSA) for the 2016-2020 period; 14 ICB samples were obtained using the saturated sample technique. The data used is secondary data derived from the annual report of each bank. Data analysis techniques using structural equation modelling (SEM) with the help of AMOS 26 software include classic assumption tests, model feasibility, and hypotheses. The results of this study indicate that zakat funds and ISR do not affect bank performance as a proxy for return on assets (ROA). However, non-halal funds significantly negatively affect ROA. Zakat funds do not affect the company's reputation proxied by market share. However, non-halal funds significantly negatively affect market share, and ISR significantly positively affects market share. This research can contribute to proving whether signalling theory, stakeholder theory, and sharia enterprise theory can strengthen or weaken the influence of zakat funds, non-halal funds, and ISR on the performance and reputation of ICB and can become reference material for Islamic banks to improve their performance and reputation.